The Use of Sitcom as Media to Improve Students’ Ability in Translating Grammatical Equivalence - Aisyah, Siti; Ariani, Musli; Puspa, Areta (EFL Education Journal, 2023)
This study is aimed at investigating the difficulties and ineffectiveness of teaching translation and gaining significant development from the students. It highlights the use of popular media in the form of audio-visual to reinforce English grammatical structures as well as its cultural aspects for the students' better comprehension in English to Indonesian translation skill. The implementation of classroom action research that includes using audiovisual media to enhance their translation skill and it’s effectively was further determined through observation and close analysis. The data was analyzed using an analytical scoring rubric to present the results of pre/post tests and classroom observation. The average of the post-test score was 79.15, indicating an improvement after the implementation of using teenage American sitcom as learning media for translation skill in the aspect of grammatical equivalence. This suggests that alternative media learning with audiovisual elements as the American teenage sitcom "Sam and Cat" was effective in teaching translation with grammametric equation. This is evidence of how the implementation process and teacher's guidance can help students improve the material and understand the concept of using audio visual media as learning medium better. The results of this study are expected reliable and solid research source for the other researchers in the same field of education in the future, especially in the topic of determining the method in enhancing students' ability in language translation.